Processos identitários e a produção da presença chinesa em Aracaju - Goes, Allisson Gomes dos Santos (2013)
This work aims to understand identity processes created because and within Chinese immigrants in Aracaju. The research problem refers to the production of Chinese presence from the economic perspective in Aracaju. This work enrolls on international migration studies, precisely between those dedicated to migratory processes to Brazilian northeast in recent years. This work also enrolls on the debate about identities and uses the field as analytical parameter. This work understand identity notion like power relations which generate location, classification and ranking, and also contestation and transgression. The use of field framework justifies itself by allowing an analytical construction of challenges and tensions, necessary to identity production. Due to the empirical scenario and a view that it was not intended to study samples, it was more appropriate replace sample notion with corpus research notion, in other words, a data set direct related to my study object. In this way, I used research procedures from document search, oral sources and direct observation. Results show identity processes in Aracaju may be understood by dialectic relations. Thereby, there is no sense on being Chinese. Being Chinese is built by nominations, a game in which Chinese names themselves and also are named by others. Brazilians say what Chinese are and, on the other hand, Chinese resists to these nominations with an almost unanimous economic consensus. Finally, Chinese presence is being made on oppositions (positive-negative) as a result of disturbs that a foreigner presence causes, especially, in economic field.